Organizational Adaptability Influenced by Practice Strategy, Environmental Dynamism, and Absorptive Capacity - Yunhao Gong; Yun Le; Xinyue Zhang; Xiaoyan Chen; Hui Zeng (Complexity)
The adaptability of organizations to their environment has always been a key concern in both organizational theory and management practice. Different from the single perspective of previous studies, this research adopts an integrated, outside-in perspective. Employing an agent-based simulation model (ASM) and a multiple regression model (MRM), we examine the impact of the intensity of exploitative and exploratory practice on organizational adaptability, as well as the moderating effect of environmental dynamism and organizational absorptive capacity. The results of the research show that (1) the stable environment prefers organizations with a practice strategy of high exploitation and low exploration; (2) environmental dynamism inhibits the impact of both exploitative and exploratory practices on organizational adaptability; and (3) organizational absorptive capacity significantly reinforces the link between the intensity of exploitative practice, as well as exploratory practice, and organizational adaptability. The study investigates the external alignment of organizational exploratory and exploitative practices with environmental dynamism and internal fit with absorptive capacity. The findings provide new insight into the question of how organizations can resist the erosion of environmental dynamism through strategic alignment and capacity development.